Human-induced rapid siltation within a macro-tidal bay during past decades - Liu, Yifei; Xia, Xiaoming; Wang, Xinkai; Cai, Tinglu; Zheng, Jun (Frontiers in Marine Science, 2024)
Tidal bay evolution is the result of the comprehensive influence of multiple factors. It is crucial to analyze the primary factors to disassemble the comprehensive effects. In this study, remote sensing and bathymetric data were used to investigate anthropogenic activities and geomorphological changes in Puba Bay, China. From 1964 to 2020, the intertidal zone area decreased by 64.5% due to mariculture ponds and coastal reclamation, with the former accounting for 60.4% of the total area. Over five decades, the bay experienced significant silting, with a 61.5% decrease in underwater area, an 88.4% decrease in volume, and considerable reductions in maximum water depth, cross-sectional terrain depth, and width. Anthropogenic activities led to a reduction in tidal prism and tidal velocity, resulting in increased flood dominance and decreased ebb dominance in the main channel, leading to more siltation. Negative and positive feedback mechanisms were observed between anthropogenic activities, seaward expansion of intertidal flats, and bay siltation. The influence of mariculture ponds, as the major factor, on geomorphological changes was found to be similar to that of coastal reclamation. To maintain water depth and capacity for material exchange in the bay, preliminary suggestions for mariculture pond management are proposed.